HUBUNGAN PENGETAHUAN KESEHATAN DAN KESELAMATAN KERJA (K3) TERHADAP HASIL BELAJAR MATA PELAJARAN PRODUK CAKE DAN KUE INDONESIA DI SEKOLAH MENENGAH KEJURUAN - Ahmad Imam Janata; Rina Setyaningsih (Universitas Sarjanawiyata Tamansiswa, 2025)
The research aims to determine: (1) the level of K3 knowledge possessed by the class, (2) student learning outcomes in the Indonesian cake and pastry products subject class, and (3) the influence of K3 knowledge on the learning outcomes of Indonesian cake and pastry products for the class. This research is a type of quantitative descriptive research. The data collection method uses correlation preceded by normality and linearity tests. The research results show that (1) the level of K3 knowledge is in the high category with a frequency of 73%. (2) learning outcomes in Indonesian cake and pastry product subjects in the category have reached the criteria for achieving learning objectives (KKTP) with a frequency of 68% (3) there is a significant positive influence between K3 knowledge on learning outcomes in class XI Indonesian cake and pastry product subjects culinary management is 35.6%, this is indicated by the value of rcount = 0.478 > rtable = 0.265 and the determinant coefficient (R2) value of 0.356.